2012
DOI: 10.3141/2320-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mobility-Impaired Persons and Analysis of Their Travel Behavior and Needs

Abstract: Mobility is an important prerequisite for equal participation in social life and satisfaction of basic human needs. Mobility impairments can restrict the participation in social life of those affected such that people lack fair opportunities for fulfilling their needs. In the past, mobility problems of people with a physical or sensory disability were the focus of attention, while other attributes causing mobility impairment, such as immigrant backgrounds, poverty, and so forth, were mainly ignored by research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…On the other hand, if there is no way to get to a station or bus stop-no matter how accessible the route is, then it could be argued that the provision of special transport enables people with transport restrictions to make necessary journeys. To be genuinely effective, special transport needs to be included as part of a wider package of measures to address barriers to access and inclusion, such as increased and accessible information and financial aids, such as concessionary travel passes [37] (p. 54).…”
Section: Transport Services Availablementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, if there is no way to get to a station or bus stop-no matter how accessible the route is, then it could be argued that the provision of special transport enables people with transport restrictions to make necessary journeys. To be genuinely effective, special transport needs to be included as part of a wider package of measures to address barriers to access and inclusion, such as increased and accessible information and financial aids, such as concessionary travel passes [37] (p. 54).…”
Section: Transport Services Availablementioning
confidence: 99%
“…Moreover, he suggests that current subsidies in South Africa actively disincentivise older adults from using public transport. Sammer et al [37] go even further in highlighting the intersecting, and accumulating nature of transport inequalities, referring to 'mobility impairment' more broadly: "In the past, mobility problems of physically disabled or sensory-disabled people were the focus of attention, whereas, more recently, problems of the elderly have been recognized as well. However, if such problems concern other groups, such as immigrants and people with learning disabilities, they have been more or less neglected" [37] (p.46)…”
Section: Intersectionalities Inequalities and The Lifespanmentioning
confidence: 99%
“…An Austrian study investigating the mobility patterns and barriers of 15 different groups of transportation disadvantaged people (e.g. people with physical or sensory disabilities, people at risk of poverty, single parents) showed that older people in particular experience barriers related to lack of accessibility to the physical environment, insufficient provision of information and inadequate public transport services (Sammer et al 2013 ). All of these aspects specifically affect people who are dependent on the use of public transport services.…”
Section: Mobility Patterns and Barriersmentioning
confidence: 99%
“…Traveller input came from answers to surveys and feedback from interviews with an assistive care community group. Sammer et al (2012) led a more in-depth analysis of the specific needs and experiences of impaired-mobility travellers. In addition to surveys, they used face-to-face interviews to collect information about trips and personal attitudes to social and transport issues with their impairments, and thus set up a typology of problems based on respondents' answers.…”
Section: Identification Of Travel Problemsmentioning
confidence: 99%